Monetary Policy Surprise Shocks under Different Fiscal Regimes: A Panel Analysis of the Euro Area - António Afonso; José Alves; Serena Ionta (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the effect of monetary policy surprise shocks on real output and the price level, conditioned on different fiscal stances in the period 2001Q4-2021Q4 for a panel of the 19 countries of the Euro Area. Applying local projection methodology, we find that the effect of monetary shocks depends on each country's fiscal stance, specifically, if for output response the debt is more important in the effect of monetary policy, for prices, the "Ricardian" nature of fiscal policy appears to be far more crucial. However, regarding inflation targeting, monetary policy is most effective in the low debt regime and in the high fiscal sustainability one. Our results are robust to different specifications and models and have important policy implications notably for monetary policy, which should consider different fiscal stances when pursuing specific monetary policy objectives.
Keywords: C32; E58; E62; E63; 330; monetary policy surprises; public debt; fiscal sustainability; local-projection models; fiscal-monetary policy mix; Euro area